Dynamic fracture with a continuum‐kinematics‐based peridynamic and a phase‐field approach. Issue 1 (24th March 2023) - Friebertshäuser, Kai; Thomas, Marita; Tornquist, Sven; Weinberg, Kerstin; Wieners, Christian
Abstract: The notion of dynamic fracture with continuum‐kinematics‐based peridynamics is presented in this work. A geometrically precise version of peridynamics called continuum‐kinematics‐based peridynamics adds surface‐ or volume‐based interactions to the traditional peridynamic bonds, accurately capturing the finite deformation kinematics. The point families produced from the horizon of the material points are used to construct the surfaces and volumes taken into account for these non‐local interactions. In continuum kinematics‐based peridynamics, the traditional bond‐stretch damage technique is insufficient for fracture. Due to the loss of strength in the internal force densities of the material points, it is now extended to the surface‐ and volume‐based interactions by new failure factors. Numerical examples demonstrate that the proposed approach effectively manages crack propagation, impact damage, and spontaneous crack initiation under dynamic loading circumstances with large deformations. When the results are compared to phase‐field calculations, there is a remarkable agreement concerning the damage patterns.